Minority carrier lifetime in HgCdTe(100) epilayers and their potential application to background radiation limited MWIR photodiodes. (29th March 2021) - Kopytko, M; Sobieski, J; Gawron, W; Kębłowski, A; Piotrowski, J
Abstract: Measurements of minority carrier lifetime have been carried out on nonintentionally doped HgCdTe(100) layers grown by metal organic chemical vapor deposition on GaAs substrates. The studies have been carried out in order to investigate the possibility of applications of HgCdTe(100) epilayers to fully depleted P–i–N photodiodes operated at near-room temperatures and the background-radiation limit. Post-growth annealed layers show n -type conductivity with a residual donor concentration of about 10 15 cm −3 . The cadmium molar composition (0.262 < x < 0.336) was chosen for mid-wave infrared devices operating at 230 K to 300 K. Results show that at high temperatures, the samples show clearly Auger-limited lifetimes determined by the background doping. The measured lifetimes at 300 K range from 5 to 11 µ s, and from 0.2 to 1 µ s, for the cut-offs of 4 µ m and 5.4 µ m, respectively.